2022
DOI: 10.1111/cup.14373
|View full text |Cite
|
Sign up to set email alerts
|

FLI‐1/Melan‐A dual stain is an alternative to PRAME in differentiating metastatic melanoma from nodal nevus: A monocentric retrospective study

Abstract: Melanocytic nevi existing in lymph nodes create a diagnostic challenge by mimicking metastases. PReferentially expressed Antigen in MElanoma (PRAME) immunohistochemical (IHC) stain can differentiate one from another. FLI‐1 IHC expression has been shown in malignant melanoma with variable sensitivity while melanocytic nevi were reported to be negative. We hypothesized that FLI‐1/Melan‐A dual IHC staining may be used in the distinction of metastatic melanoma from nodal nevi and can be an alternative and/or compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Another study demonstrated high sensitivity (94%) and specificity (100%) for detecting metastatic melanoma utilising a parameter of > 50% staining for PRAME 75 . A very recent study of FLI‐1 IHC expression in 26 lymph nodes (13 NMN, 13 melanoma metastases) showed comparable sensitivity and specificity to PRAME when a FLI‐1/Melan‐A dual stain was utilised 77 …”
Section: New Considerations In Evaluating Tumour Burdenmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study demonstrated high sensitivity (94%) and specificity (100%) for detecting metastatic melanoma utilising a parameter of > 50% staining for PRAME 75 . A very recent study of FLI‐1 IHC expression in 26 lymph nodes (13 NMN, 13 melanoma metastases) showed comparable sensitivity and specificity to PRAME when a FLI‐1/Melan‐A dual stain was utilised 77 …”
Section: New Considerations In Evaluating Tumour Burdenmentioning
confidence: 99%
“…75 comparable sensitivity and specificity to PRAME when a FLI-1/Melan-A dual stain was utilised. 77 SOX10, a nuclear transcription factor, has been under investigation as an alternative for S100 as it appears to have higher specificity than S100 and avoids background dendritic cell staining and increased sensitivity compared to HMB-45 and Melan-A 62,68,78,79 However, similar to S100, SOX10 stains nodal naevi, lending limited utility to its use in differentiating between NMN and metastatic melanoma. 62,80 The number of CD3 + , CD4 + and CD8 + lymphocytes present in sentinel node deposits, detected on IHC, has also been positively correlated with recurrence-free and overall survival.…”
Section: S U R F a C E A R Ementioning
confidence: 99%
“…90 Two additional smaller series showed similar findings for PRAME IHC in nodal melanocytic deposits, with predominantly absent to rare nondiffuse PRAME staining in nodal nevi, typically diffuse PRAME immunoreactivity in most metastatic melanoma deposits, and high concordance in PRAME expression status between primary cutaneous melanomas and subsequent lymph node metastases, supporting PRAME IHC role in this setting. 91,92…”
Section: Prame In Metastatic Melanoma and The Assessment Of Nodal Mel...mentioning
confidence: 99%
“…90 Two additional smaller series showed similar findings for PRAME IHC in nodal melanocytic deposits, with predominantly absent to rare nondiffuse PRAME staining in nodal nevi, typically diffuse PRAME immunoreactivity in most metastatic melanoma deposits, and high concordance in PRAME expression status between primary cutaneous melanomas and subsequent lymph node metastases, supporting PRAME IHC role in this setting. 91,92 Morphologic assessment of nodal melanocytic deposits on H&E routine sections remains paramount. In addition, correlation of morphologic features between the primary tumor and suspected metastasis as well as knowledge of the PRAME expression status of the primary melanoma are always important.…”
Section: Prame In Metastatic Melanoma and The Assessment Of Nodal Mel...mentioning
confidence: 99%